Targeting Spleen Tyrosine Kinase-Bruton's Tyrosine Kinase Axis for Immunologically Mediated Glomerulonephritis. (30th March 2014) - Chen, Jin-Shuen; Chang, Li-Chien; Huang, Shyh-Jer; Cheng, Chao-Wen
Abstract : The importance of B-cell activation and immune complex-mediated Fc-receptor activation in the pathogenesis of immunologically mediated glomerulonephritis has long been recognized. The two nonreceptor tyrosine kinases, spleen tyrosine kinase (Syk) and Bruton's tyrosine kinase (Btk), are primarily expressed by hematopoietic cells, and participate in B-cell-receptor- and Fc-receptor-mediated activation. Pharmacological inhibitors of Syk or Btk are undergoing preclinical development and clinical trials for several immune diseases; and Syk inhibitors have been shown to reduce disease activity in rheumatoid arthritis patients. However, the clinical therapeutic efficacies of these inhibitors in glomerulonephritis have not been evaluated. Herein, we review recent studies of Syk and Btk inhibitors in several experimental primary and secondary glomerulonephritis models. These inhibitors suppressed development of glomerular injury, and also ameliorated established kidney disease. Thus, targeting Syk and Btk signaling pathways is a potential therapeutic strategy for glomerulonephritis, and further evaluation is recommended.